Moving MarketPlaces (MMP): Following the Everyday Production of Inclusive Public Spaces - (:unkn) unknown (My University, 2025)
While most research focuses on how marketplaces are consumed, MMP concentrates on the actors that make markets work: the merchants. Investigating both rural and urban marketplaces across four countries (Spain/Switzerland/the Netherlands/UK), MMP not only pays attention to merchants’ place-making capacities, but also to their mobility practices. Following merchants from market to market, this translocal perspective helps to deepen theoretical and empirical understandings of how marketplaces are produced as inclusive spaces. The collaborative research project is part of the HERA Joint Research Programme “Public Spaces: Culture and Integration in Europe”.
Keywords: public spaces; mobility; market